The effect of albumin fusion structure on the production and bioactivity of the somatostatin-28 fusion protein in Pichia pastoris. (1st June 2014) - Ding, Yuedi; Fan, Jun; Li, Wenxin; Peng, Ying; Yang, Runlin; Deng, Lili; Fu, Qiang
Abstract: Somatostatin, a natural inhibitor of growth hormone (GH), and its analogs have been used in clinical settings for the treatment of acromegaly, gigantism, thyrotropinoma, and other carcinoid syndromes. However, natural somatostatin is limited for clinical usage because of its short half-life in vivo. Albumin fusion technology was used to construct long-acting fusion proteins and Pichia pastoris was used as an expression system. Three fusion proteins (SS28)2 -HSA, (SS28)3 -HSA, and HSA-(SS28)2, were constructed with different fusion copies of somatostatin-28 and fusion orientations. The expression level of (SS28)3 -HSA was much lower than (SS28)2 -HSA and HSA-(SS28)2 due to the additional fusion of the somatostatin-28 molecule. MALDI-TOF mass spectrometry revealed that severe degradation occurred in the fermentation process. Similar to the standard, somatostatin-14, all three fusion proteins were able to inhibit GH secretion in blood, with (SS28)2 -HSA being the most effective one. A pharmacokinetics study showed that (SS28)2 -HSA had a prolonged half-life of 2 h. These results showed that increasing the number of small protein copies fused to HSA may not be a suitable method for improving protein bioactivity.